Introducing Resilience Practice to Watershed Groups: What Are the Learning Effects?. Issue 10 (2nd October 2016) - Baird, Julia; Plummer, Ryan; Moore, Michele-Lee; Brandes, Oliver
ABSTRACT: Resilience as an organizing framework for addressing dynamics of social–ecological systems has experienced strong uptake; however, its application is nascent. This research study aimed to address the gap between resilience thinking and practice by focusing on learning, a key aspect of resilience. Two Canadian watershed groups were led in 2-day workshops focused on resilience. Learning effects were measured using a survey administered both before and after the workshop, and a qualitative survey was administered 6 months later to understand longer term effects. Short-term learning effects were similar between the two case studies, with strong cognitive and relational learning and less normative learning. Longer term effects showed enduring cognitive and normative learning in both cases; however, relational learning persisted only in the watershed where a resilience practice approach to watershed planning had been incorporated. Future research directions include refinements to the learning measurement methodology and continuing to build resilience practice literature.